Peer Instruction Using PhET Integrated with Inquiry-based Learning in Kinematics Physics Learning - Pranata, Ogi Danika (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2024)
This study investigates the impact of integrating peer instruction with PhET simulations and inquiry-based learning on physics education. Given the constraints of having only one class of 40 students, a one-group quantitative design was employed, complemented by a qualitative approach to create a mixed-method design. Quantitative analysis of pre-test and post-test results was performed using N-Gain, effect size, and paired samples t-test. Furthermore, qualitative analysis provided insights into students' learning experiences. The average N-Gain score initially showed a low increase (0.26), but excluding cases with negative gains revealed a moderate increase (0.38). The paired samples t-test confirmed a significant improvement in post-test scores compared to pre-test scores, with a large effect size (), demonstrating the effectiveness of the intervention. However, further analysis is needed to explore the distribution of student answers and underlying misconceptions. Some misconceptions were corrected, such as those related to distance, displacement, and velocity equations. However, kinematics graphs and vertical motion persisted. This finding underscores the urgency of refining teaching methods to address these persistent issues. The findings highlight the potential of this integrated approach to improve physics instruction and suggest that educators can use these insights to better support students' understanding of kinematics and graphical analysis.